Patterns of Democracy Matter in the COVID-19 Crisis - Nils C. Bandelow; Patrick Hassenteufel; Johanna Hornung (International Review of Public Policy)
COVID-19 poses a new challenge to governmental decision-making. With a great level of uncertainty regarding the roots, distribution, prevention, and effects of the pandemic, and with scientific insights and recommendations changing on a daily basis, politicians face the difficult task of reacting quickly but justifiably to the developments. Neo-institutional perspectives of policy research can contribute to the understanding of similarities and differences in strategies to deal with the pandemic by focusing on the interrelationship of institutions and the policy process. A comparison of France and Germany highlights the effects of different patterns of democracy. In what way does the national institutional setting, particularly federalism and centralization, contribute to decision-making? How are political decisions instrumentalized in public debates? The findings indicate that the different patterns of democracy in France (unitary majoritarian system) and Germany (federal consensus system) provide distinctive challenges and make it difficult to transfer successful policies from one country to another.